Best estimate of the magnitude of mortality due to occupational exposure to hazardous substances. Issue 9 (September 1998) - Morrell, S; Kerr, C; Driscoll, T; Taylor, R; Salkeld, G; Corbett, S
Abstract : OBJECTIVES: With a proportionate attributable risk approach, to estimate the magnitude of premature mortality induced by exposure to hazardous substances in the Australian workforce. METHODS: Estimates of the magnitude of mortality induced by exposure to hazardous substances in the Australian work-force were calculated by the proportionate attributable risk approach after careful consideration of options for methodological refinements. The main data sources used were unit mortality datasets (individual deidentified death records), and tabulations when these were unavailable. RESULTS: The estimated number of deaths that occurred in Australia each year from occupational exposure to hazardous substances was 2290; 78% of these were men. The rate of mortality attributable to occupational exposure to hazardous substances was three to four times greater in male workers than in female workers. Male (productive) person-years of life lost (PYLL) were generally eight times higher than female PYLL. Cancer was the prime cause of death, followed by renal, cardiovascular, neurological, and chronic respiratory disease. Acute toxic episodes accounted for a small proportion of mortality but yielded a much larger proportion of PYLL, reflecting the relatively young ages of those who experienced fatal effects. CONCLUSIONS: Although national estimates of the proportions of mortality attributable to occupational exposure to hazardous substances seemed to be validly derived, uncertainties remain associated with the lack of an empirical basis for derivation of proportionate risk fractions used in the calculations. The finding of an appreciable burden of mortality that is attributable to past occupational exposure to hazardous substances emphasises the necessity for occupational health and safety authorities to measure and reduce worksite exposures. There is also an incentive to encourage the construction of appropriately designed cohort studies across industries and occupational groupings so that, ultimately, risk estimates may be directly calculated and applied to total workforce data for the definitive estimation of the magnitude of harm induced by occupational exposure to hazardous substances.